2015
DOI: 10.24926/ijps.v2i1.104
|View full text |Cite
|
Sign up to set email alerts
|

Caring International Research Collaborative: A Five-Country Partnership to Measure Perception of Nursing Staffs’ Compassion Fatigue, Burnout, and Caring for Self

Abstract: Partnering in research across disciplines and across countries can be challenging due to differing contexts of practice and culture. This study sought to demonstrate how central constructs that have application across disciplines and countries can be studied while concurrently considering context. Groups of nurses from Botswana, Ireland, Israel, New Zealand, and Spain partnered to identify how to measure the constructs of caring for self, burnout, and compassion fatigue, replicating a study by Johnson (2012), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The results of the current analysis suggest that resilience explains a significant part of the relationship with burnout. Findings support the notion that the effect of workplace violence may be influenced by resilience [69]. Previous findings of a positive correlation between resilience and compassion satisfaction were supported, which in accordance with the notion that compassion satisfaction may be considered as one of the multiple pathways of resilience [70].…”
Section: Discussionsupporting
confidence: 85%
“…The results of the current analysis suggest that resilience explains a significant part of the relationship with burnout. Findings support the notion that the effect of workplace violence may be influenced by resilience [69]. Previous findings of a positive correlation between resilience and compassion satisfaction were supported, which in accordance with the notion that compassion satisfaction may be considered as one of the multiple pathways of resilience [70].…”
Section: Discussionsupporting
confidence: 85%
“…This is not to say that these issues are not an international problem. Many studies have pointed to the global scope of the problem (Itzhaki et al, 2015; Zhang, Han, et al, 2018; Zhang, Zhang, et al, 2018). Further study could be done to explore the impact of different models of health‐care, private vs. public for example, which is outside the scope of this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Canfield (2005) asserted that self-care could prevent exposure to STS from developing into a chronic disorder. In support, Itzhaki et al (2015) found that self-care moderated burnout and CF in nurses in a five-country study. This could be interpreted relative to Kotaro et al (2015) and Lazarus and Folkman's (1984) theories that burnout depletes resources; self-care may build up (coping) resources which reduce the likelihood of exposure to traumatic material resulting in STS.…”
mentioning
confidence: 92%